Impacto de las estrategias de responsabilidad social empresarial de la minera Barrick lagunas norte en el distrito de Quiruvilca. - Silva Solano, Sheila Guisella (2011)
The miners companies since the appearance in Peru have had a great success, so much that have turned into the principal support of the Peruvian development and same time it’s the sector with more income in level nacional, but The Libertad isn’t foreign to this growth, taking as a principal company the miner Barrick who dedicates to the exploitation of gold, motive for which there are many hopes of how the miner Barrick takes part actively in the development of Quiruvilca's district, by strategies of corporate social responsibility. The reason to present work of investigation that I developed with the purpose of knowing which is the cognitive, affective and behavioral impact of the strategies of social managerial responsibility implemented by the miner Barrick in Quiruvilca's district, since the above mentioned company comes working in the mentioned district. To realize this study I realize a descriptive investigation transverse simple, by means of the use of application of surveys to the people from of Quiruvilca's district, which it had as principal result that the impact of the strategies of social managerial Responsibility implemented by the Miner Barrick, in Quiruvilca's district it’s relatively beneficial in programs such a health, education, productive activities and community infrastructure